2016
DOI: 10.17665/1676-4285.20164233
|View full text |Cite
|
Sign up to set email alerts
|

Banho no leito de infartados: crossover do controle hidrotérmico 40ºC versus 42,5º

Abstract: Aim:  To  compare  the  results  of  the  water  used  to  bath  infarcted patients  in  bed  under  oxy-hemodynamic  variables.  Method:  This  research  uses  a  2X2 crossover of the interventions: bed bath with constant water temperature at 40°C (BB1) and 42.5°C (BB2) in 20 patients who had acute myocardial infarction (AMI). Dependent variables  are:  pulse  oximetry,  cardiac  frequency  (CF)  and  axillary  temperature  (Axt). The  inferential  statistics  will  be  used  in  an  analysis  of the  variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Few studies have addressed the body temperature after hygiene care. In one study in cardiology patients, da Silva et al 28 reported an increase in body temperature when using a water temperature of 42.5°C. In our study, we found a significant decrease in body temperature both during night and day bed baths.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have addressed the body temperature after hygiene care. In one study in cardiology patients, da Silva et al 28 reported an increase in body temperature when using a water temperature of 42.5°C. In our study, we found a significant decrease in body temperature both during night and day bed baths.…”
Section: Discussionmentioning
confidence: 99%
“…Because AHT10s has a significantly short duration and provides warmth and comfort to healthy and elderly adults' forearm and back , it may solve the dilemma of bed baths in clinical practice. Furthermore, by adjusting the hot water temperature to 40-42.5°C depending on the patient's preference and condition (Silva et al, 2016) and combining with dry wiping to avoid maceration and undue cooling, it seems possible to efficiently provide warmth and comfort to the patient.…”
Section: Bed Bath Methods For Enhancing Comfortmentioning
confidence: 99%
“…Three studies performed interventions regarding differences in thermal stimulation Silva et al, 2016).…”
Section: Thermal Stimulationmentioning
confidence: 99%
See 1 more Smart Citation